Latent of The Victims: Perlakuan Terhadap Anak Paska Mengalami Kekerasan Seksual - Henky Fernando; Yuniar Galuh Larasati; Agus Indiyanto; Riky Novarizal; Syahrul Akmal Latif (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2023)
The treatments of children after experiencing sexual violence from their social structure does little to make children become victims again in the process of resilience. Studies that have discussed this context have only focused on handling the victim's condition, so they have not comprehensively explained the treatment received by the victim. This study focuses on the question